Familial dilated cardiomyopathy: a worse prognosis compared with sporadic forms. Issue 2 (August 1995) - Csanády, M.; Högye, M.; Kallai, A.; Forster, T.; Szárazajtai, T.
Abstract : OBJECTIVE–To establish the time of onset of dilated cardiomyopathy (DCM) by review of annual chest x rays, which are obligatory in Hungary. DESIGN–A retrospective survey of chest x rays of a cohort of confirmed cases of DCM, to assess time of onset of cardiomegaly. Clinical course was compared by follow up over a mean of six years from the time of diagnosis. SUBJECTS–240 patients with DCM (31 familial, 209 non-familial). Diagnosis was made by echocardiography in all cases and confirmed by coronary angiography and heart biopsy in some cases. MAIN RESULTS–At diagnosis, the mean age of the patients was 31.8 years in the familial group and 39.6 years in the non-familial group (P < 0.05). The time between the onset of cardiomegaly (cardiothoracic ratio > 0.45) and clinical diagnosis was 8.0 and 10.1 years respectively (P < 0.05). The six year survival was 6% in the familial group and 23% in the non-familial group (P < 0.05). CONCLUSIONS–The familial form of DCM is the more malignant form: it occurs at an earlier age and progresses more rapidly than non-familial DCM.